Association of the Healthy Eating Index (HEI) Score of Children Enrolled in School Lunch and Breakfast Program and Frequency of Meals at School: NHANES 2015–2016. (29th May 2020) - Shankaranarayanan, Kavitha; Miketinas, Derek
Abstract: Objectives: Nutritious and well-balanced school meals are critical to curbing the obesity epidemic in school-aged children while also providing adequate nutrition to sustain healthy growth and development. The school lunch program underwent a significant revamp in 2012 to align the menu with the US Dietary Guidelines. The Healthy Eating Index (HEI) is a metric that measures this alignment. The purpose of this study is to calculate usual HEI scores for children and compare HEI scores across frequency of school meals consumed using NHANES 2015–2016. Methods: Children 18y and younger were included in the analyses and categorized into one of five groups for breakfast and lunch, each. Either consuming no school breakfast/lunch or consuming school breakfast/lunch 1–5 times daily. Usual HEI scores and standard errors were determined using the NCI method. Independent samples t-tests were computed for pairwise comparisons between no school breakfast/lunch consumption and increasing frequency of consumption. All analyses were performed using SAS version 9.4. Results: Mean HEI scores for children consuming 0, 1, 2, 3, 4, 5 school breakfasts per week was 44.7 ± 0.8, 44 ± 1.9, 41.4 ± 2.4, 43.9 ± 1.4, 40.8 ± 2.3, 42.7 ± 1.0 and the mean HEI score for children consuming 0, 1, 2, 3, 4, 5 lunches per week was 44.7 ± 0.8, 46.7 ± 0.8, 42.3 ± 2.5, 45.0 ± 0.9, 46.1 ± 0.9, 43.3 ± 0.8, respectively. These results indicate that there are no significant differences across children who consumed these meals at various frequencies with those that do not consume school meals. Although there were no observed differences, overall diet quality was poor for those who do and do not consume school breakfast/lunch. Conclusions: Although children and adolescents who consumed school breakfast/lunch did not appear to have greater diet quality than those who did not, overall diet quality was poor for all groups. Therefore, additional efforts are needed to improve diet quality in children and adolescents. Funding Sources: Texas Woman's University.